Asas Legalitas Tindak Penyalahgunaan New Psychoactive Subtances Dalam Kajian Hukum Pidana - Alfredo Risano (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2021)
Legal consequences of the legality principle if it is related to narcotics that are not regulated in law. About New Psychoactive Subtances, Through extensive interpretation, the judge expands the meaning of special provisions into general provisions in accordance with grammatical rules, so the judge must make legal findings in adjudicating narcotics crime cases new types, this is done because new types of narcotics are not included in the attachment to Law Number 35 of 2009 concerning Narcotics.